Mixed convection about a rotating sphere - Ecder, Ali. (Thesis (M.S.)- Bogazici University. Institute for Graduate Studies in Science and Engineering, 1986., 1986)
This report presents a theoretical analysis of flow and heat transfer characteristics of the effects of rotational speed, buoyancy force and the Prandtl number on laminar boundary layer over a rotating sphere in forced flow. Applying the finite difference method, numerical computations are carried out for various values of the above parameters. Both assisting and opposing flows are considered. Although the heating condition of uniform wall tempeuture is used in the analysis, the case of uniform surface heat flux is also studied in the formulation. After an introduction to the subject and an examination of the previous works, the theoretical background chapter supplies a general formulation. In the seotion which follows, the problem is specified. Then the results of the numerical solution are displayed in graphical form. Finally, the results are discussed and conclusions are arrived at. The computer program is also supplied.
Keywords: Heat -- Transmission.; Mass transfer.